Company characteristics and the extent of corporate social responsibility disclosure among public listed companies in Malaysia / Dyana Awang Sahdi - Awang Sahdi, Dyana (2015)
Corporate social responsibility (CSR) disclosure can be defined as the provision of information regarding human resource aspects, product and service, involvement in community projects including philanthropic activities and environmental matters. Current globalization trend and growing demand from stakeholders toward companies in adopting (CSR) practices have encouraged the involvement of companies in CSR practices. Corporate govemace is about managing the company's performance of business corporations to get more rate of return. The specific objectives of this dissertation are: (1) to examine the extent of CSR disclosures among top-public listed companies in Malaysia after the changing in codes of corporate governance announced by the Malaysian Code on Corporate Governance 2012 (MCCG 2012), and (2) to examine the effect of company characteristics such as board size, type of industry, profitability, leverage, and CEO duality on the extent of CSR disclosures among the top 100 Malaysian public listed corporations, using legitimacy theory. This research employed a quantitative research design and the population studied consisted of the public listed companies in Malaysia. Content analysis and a CSR disclosure checklist were used to measure the extent of CSR disclosure in annual reports for the year ending 2013 and multiple regression analysis was applied to examine the significant relationship between companies' characteristics and the extent of CSR disclosure in annual reports. It was found that even among different industries in Malaysia, there was considerable variability in the amount of social activities disclosed in corporate annual reports. Results from the multiple regression analysis showed that, consistent with expectations, companies that had higher profitability disclosed significantly more CSR information, while companies that had a large board size, higher leverage, and CEO duality disclosed insignificantly less CSR information. In general, results also found that the extent of CSR disclosure was significantly positively related to the companies' financial performance, which signifies that companies may strategically use investment in CSR activities to improve their profitability and remain consistent with the changes in the MCCG 2012. It is recommended that there should be more vibrant strategies by the Malaysian government to ensure all public listed companies comply with CSR disclosure regulations. For example, there should be mechanisms of enforcement. The significance of this dissertation is that Malaysian regulatory authorities can draw on its results to revise existing codes on corporate governance in order to enhance the governance and accountability practices of Malaysian listed companies.